2015
DOI: 10.1016/j.mee.2015.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Pockels effect in ferroelectric barium titanate thin films on Si(0 0 1)

Abstract: a b s t r a c tHigh-quality epitaxial BaTiO 3 (BTO) on Si has emerged as a highly promising material for future electrooptic (EO) devices based on BTO's large effective Pockels coefficient. We report on the EO response of BTO films deposited on Si by molecular beam epitaxy (MBE), and characterize the structure of these films by reflection high-energy electron diffraction and X-ray diffraction. O 2 rapid thermal anneal at 600°C for 30 min ensures full oxidation of BTO for minimal leakage current with minimal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
(21 reference statements)
0
38
0
Order By: Relevance
“…More details of the experimental system can be found elsewhere. [185] All substrates were outgassed in the MBE chamber at 700° for 10 min under ultra-high vacuum (UHV). The substrate temperature was measured by a thermocouple (calibrated by pyrometer measurement of a silicon substrate) in proximity to the substrate heater.…”
Section: Film Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…More details of the experimental system can be found elsewhere. [185] All substrates were outgassed in the MBE chamber at 700° for 10 min under ultra-high vacuum (UHV). The substrate temperature was measured by a thermocouple (calibrated by pyrometer measurement of a silicon substrate) in proximity to the substrate heater.…”
Section: Film Depositionmentioning
confidence: 99%
“…Since these components have been mastered in bulk telecommunication applications by the usage of materials with strong electro-optical properties such as lithium niobate, [50] a concerted effort has emerged to integrate similar materials into silicon photonic structures, where the refractive index index n can be expressed in terms of the static external electric field E, [222] where n0 is the zero-field value of the refractive index and r is the Pockels coefficient. In particular, the recent integration of barium titanate (BaTiO3) on silicon with large Pockels coefficients [63,67,72,185] opens an exciting opportunity for designing and realizing high-speed modulators, and novel device types such as nonvolatile optical memories. The latter elements would be of great interest as synaptic elements for optical neural networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Chern et al demonstrated epitaxial growth of barium titanate by the same precursors, but at lower temperatures (680 °C) and for relatively large lattice mismatches between film and substrates (4%-6% for LaAlO 3 and NdGaO 3 ) when using plasma enhanced (PE)CVD. [10] Gorbenko et al also demonstrated epitaxial growth on MgO, SrTiO 3 , and ZrO 2 by aerosol-CVD utilizing Ba(tmhd) 2 -2Phen and Ti( i OPr) 2 (tmhd) 2 . [11] A solution of Ba(thmd) 2 and Ti( i OPr) 2 (tmhd) 2 in n-butyl acetate and tetraglyme is suitable for single source epitaxial MOCVD on LaAlO 3 and MgO as shown by Zhao et al [8] However, we have shown that this type of precursor chemistry fails in high vacuum (HV-)CVD conditions due to a surface passivation effect upon barium hexafluoroacetylacetonate exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Using this chemistry, however, the formation of epitaxial or textured thin barium titanate films require high temperatures above 550 °C, which is not compatible with current CMOS technology. The first textured deposition of barium titanate on aluminum oxide and sodium chloride substrates by CVD has been reported by Kwak et al [6] Using carrier gas consisting of argon and oxygen, Ba(thd) 2 and Ti(O i Pr) 4 molecules were transported to the heated substrate (550-800 °C) where polycrystalline films where formed. Growth dynamics for short deposition times (15 min) on quartz resulted in a film that was highly textured in [101] direction.…”
Section: Introductionmentioning
confidence: 99%